Aplicação da coagulação/precipitação como pós-tratamento de efluente de uma indústria de papel e celulose - Kuritza, Jóice Cristini (2012)
The purpose of this study was to evaluate the use of the coagulation / flocculation / sedimentation set in the post-treatment of effluent from a treatment station from a pulp and paper mill. Tests were performed in laboratory utilizing jar-test instruments to establish the best operational settings for the treatment used. The tests were divided in three steps: the purpose of the first step was to verify the treatment efficiency with individual application of coagulant (PAC - aluminum polychloride), set the operational parameters of slow mixing and sedimentation, choose the polymer to be used as an auxiliary of flocculation and to obtain a first indication of the best dosages of coagulant and polymer. In stage 02 were performed more tests of coagulation / flocculation / sedimentation testing a large range of doses of coagulation combined with different dosages of anionic polymer. Moreover, were tested shorter times of flocculation. The success of treatment was measured by removing turbidity, color apparent and true and COD and true, besides analysis of SVI - sludge volume index. In step 03 were made two tests, a coagulation / flocculation / sedimentation to define the best dosage of polymer and especially verify whether the treatment was effective at removing lignin and AOX, and an assay of microfiltration, on a pilot plant, to evaluate the system performance when applied treated effluent in the best configuration found of coagulation / flocculation / sedimentation. The results indicated that coagulation / flocculation / sedimentation has improved characteristics of the effluent, reducing turbidity up to 98%, 95% in apparent color, 93% of true color and 75% of COD using PAC dosage of 250 mg / L and 1mg / L of anionic polymer. In residual values, turbidity was reduced to 1.86 uT, the apparent color to 92uC,the true color to 79uC and COD to 78mg / L. Furthermore, there was 60% removal of AOX and 70% of lignin. The sludge generated by treatment with polymer had better sedimentability compared to the configurations in which only coagulant was used. In the use of the treated effluent by coagulation / flocculation / sedimentation in the pilot plant of microfiltration, there was significant improvement in the permeate flux in relation to the permeate flux filtration of the effluent without prior treatment. Therefore, the treatment used presented great potential for application as post-treatment of effluent from pulp and paper mill and as a pre-treating effluents from microfiltration membranes